HEALING ENVIRONMENT APPROACH TO HANDLING STRESS IN DRUG ADDICTS - Falah, Nailul; Hanan Izza Hanafi; Slamet (UIN Sunan Kalijaga Yogyakarta, 2025)
This research is motivated by the increasing number of drug abuse cases in Indonesia in recent years, which has caused anxiety for all Indonesians. Rehabilitation is one way to deal with drug abuse, although there are consequences for those who cannot adapt to the environment and the pressures of change. Stress can arise in drug addicts undergoing the rehabilitation process if they cannot adjust. However, the increase in drug cases in Indonesia is inversely proportional to data found by the author at one of the Social Welfare Institutions that cares for drug victims and participates in rehabilitating drug addicts in Indonesia, namely the Pondok Tetirah Dzikir Yogyakarta Rehabilitation Center. The author found a fairly significant decrease in data from 2021 to 2024 on students under the care of drug addicts. In this case, The Pondok Tetirah Dzikir Rehabilitation Center utilizes environmental factors and natural elements in its treatment. This study aims to determine, describe, and analyze the approach of the healing environment concept to address the stress of drug addicts at the Pondok Tetirah Dzikir Yogyakarta Rehabilitation Center. Keywords: Healing Environment Approach, Stress of Drug Addicts, Rehabilitation.